Precast tunnel segments for metro tunnel lining: A hybrid reinforcement solution using macro-synthetic fibers. (15th November 2019) - Conforti, Antonio; Trabucchi, Ivan; Tiberti, Giuseppe; Plizzari, Giovanni A.; Caratelli, Angelo; Meda, Alberto
Highlights: A novel research on the use of hybrid reinforcement in precast tunnel segments for metro tunnel lining. Successful combination of macro-synthetic fibres and bars for reinforcing precast tunnel segments. Flexural and point load tests on full-scale precast tunnel segments for metro tunnel lining. Abstract: The addition of fibers has been proven successful to simplify reinforcement in precast tunnel segments, allowing as a function of both segment typology and fiber reinforced concrete (FRC) toughness a total or partial replacement of the conventional reinforcement. Results from an experimental research aimed at comparing the structural behavior of segments made with conventional (only rebars, RC) or hybrid (rebars + fibers) reinforcement are presented. The experimental program consisted of flexural and point load tests (which reproduces the jack actions during TBM operations) carried out on four large-scale precast tunnel segments representative of a metro tunnel lining characterized by an internal diameter of 5.80 m and a thickness of 0.30 m. The main goal of the experimental program was to evaluate the possibility of using macro-synthetic polypropylene fibers (Polypropylene Fiber Reinforced Concrete, PFRC) in combination with a lower amount of conventional rebars (optimized reinforcement, RCO) for guaranteeing the required segment performance. Experimental results indicate that macro-synthetic fibers may be very effective in combination with conventional rebars to withstand the main stresses that arise in a segment both at initial and final phases, proving that the adoption of hybrid reinforcement solution using macro-synthetic fiber is possible for metro tunnel lining.